Rancang Bangun PLTS Menggunakan Sistem Hybrid Pada Rumah Tangga Untuk Menggurangi Ketergantungan Energi Listrik Dari PLN - Wahyu Bagus Rahmatulloh; Aris Heri Andriawan (Uranus: Jurnal Ilmiah Teknik Elektro, Sains dan Informatika, 2024)
Based on national policy, renewable energy is a source of energy that can be renewed, such as water, geothermal, sun, biomass, wind, changes in sea temperature, biogas, biofuel and sea waves. The sun is a type of renewable energy that is used to fulfill human needs. This condition is because the sun is basically eternal or never runs out, so its use is easier than other renewable energy. PLTS is a power plant that converts sunlight energy into electrical energy, often called a solar cell. This design is intended to study the hybrid PLTS design system to reduce dependence on electrical energy from PLN. A hybrid system is a system that uses two energy sources which will then back up each other. The results of this test in the solar panel test, the highest voltage was 17.51 ​​and the highest current produced by the solar panel was 4.12, and the battery charging test for 9 hours was 51.85Ah. Weather conditions and time differences cause the light intensity received by the panel to produce varying values, voltage, current and power due to uncertain weather conditions.